Bilateral brachio-antebrachial arterial variations with ontogenic explanation - Vasanti Arole; Vaishaly Bharambe (Medical Journal of Dr. D.Y. Patil University, 2016)
During dissection in the Department of Anatomy, a female cadaver was encountered with arterial variations bilaterally. From third part of axillary artery, a branch was observed running superficial to median nerve, which was called as superficial brachial artery. The axillary artery after passing through the two roots of median nerve continued as normal (deep) brachial artery. The course of superficial and deep brachial arteries was different on both sides. Common interosseous artery was observed as a branch of radial artery bilaterally. Also, ulnar artery was seen entering the hand passing deep to flexor retinaculum bilaterally, which may get affected in carpal tunnel syndrome. It is important for the clinicians to have knowledge of such variations. An attempt has also been made to explain the variations ontogenically.